COMPETITIVENESS STRATEGIES FOR INDONESIAN HALAL-CERTIFIED SOYBEAN DERIVATIVES IN INTERNATIONAL MARKETS: AN EXPERT-BASED SWOT-TOWS ANALYSIS - Muhammad Yusuf Ibrahim; Ruben Chandra Winata; Mohmed Firdaus Bin Masruhen (International Journal Mathla’ul Anwar of Halal Issues, 2026)
Global demand for halal-certified plant-based foods is increasing rapidly, driven by growing consumer interest in ethical, clean-label, and high-protein diets. Despite Indonesia’s strong cultural heritage in soy-based products such as tempeh and tofu, its international competitiveness remains limited. This study aims to formulate strategic priorities to enhance the global competitiveness of Indonesian halal-certified soybean derivative products. Using a qualitative expert-based approach, data were collected through in-depth interviews with key stakeholders, including halal regulators, industry practitioners, and academics, and analyzed using thematic analysis. The identified internal and external factors were structured through a SWOT framework and further translated into strategic options using the TOWS approach. The findings indicate that Indonesia’s main strengths lie in its institutionalized halal certification system, cultural expertise in fermented soybean processing, and extensive MSME base. However, competitiveness is constrained by high dependence on imported soybeans, low domestic productivity, and limited technological adoption. Externally, expanding halal and plant-based food markets offer significant opportunities, while global price volatility, intense competition, and stringent non-tariff trade standards pose key threats. The study concludes that halal certification alone is insufficient for global competitiveness, highlighting the need for integrated strategies focusing on domestic supply strengthening, MSME upgrading, and value-added product differentiation.